Preservice Teachers’ Criticality in Analysing School English Teaching Materials: Gender Representation and Islamic Perspective - Iwan Jazadi; I G A Widari; Aris Dwi Intan Aprianti (International Journal of Language Education, 2023)
This article reports on teacher trainees’ ability in doing a critical analysis of an extract of English teaching materials from a gender perspective. The critical ability was prompted using a textbook extract that generated two gender issues, namely woman-man relationship and the position of women in occupational discourse. The participants were 38 trainees enrolled in textbook analysis subject in the English Department of a college in regional Indonesia. The research data were the trainees’ results of the mid-term test, designed with explicit instruction to ascertain the afore-mentioned critical elements, and their results of the final exam with implied instruction to discern the same critical elements. The data were analysed qualitatively by interpreting the participants’ responses based on their degree of criticality. The mid-term test results show that more than half of them were critical about woman-man relationship, while only 18% were critical about women position at work. The trainees’ results in the final test demonstrate a significant downturn of their critical thinking performances. Only 15% criticized woman-man relationship and 13% problematized women position at work. These findings raise concerns about the trainees’ level of criticality and so systematic efforts to sharpen trainees’ critical analytical ability should be further attempted.